Penerapan Jelajah Kampus Virtual dalam Meningkatkan Pengalaman Orientasi Mahasiswa Kelas Karyawan Jakarta Global University - Chairil Andri; Risna Oktaviati; Hadi Wijaya (Jurnal Teknologi Informasi dan Multimedia, 2024)
New employee class students frequently encounter substantial challenges in attending on-campus orientation sessions, such as time constraints, geographical barriers, and financial burdens. This study investigates the effectiveness of implementing a virtual campus tour application in assisting new employee class students at Jakarta Global University to better acquaint themselves with the campus and prepare for academic life. By leveraging technologies such as 3D mapping, 360-degree panoramic photography, and virtual reality (VR), the virtual campus tour provides an immersive and flexible experience, allowing students to explore various campus facilities at their convenience and from any location. The development method used is Multimedia Development Life Cycle (MDLC), which encompasses needs analysis, conceptualization, design, material collection, assembly, testing, and distribution. The application underwent black box testing to ensure functionality, while student perceptions were assessed through a structured questionnaire. The research results indicate that the majority of respondents, with an average positive rating of 86.3%, agree that virtual campus tours are an innovative solution that should be adopted by universities to overcome the limitations of traditional campus orientation activities.